2017
DOI: 10.1016/j.watres.2017.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Biological attenuation of arsenic and iron in a continuous flow bioreactor treating acid mine drainage (AMD)

Abstract: Passive water treatments based on biological attenuation can be effective for arsenic-rich acid mine drainage (AMD). However, the key factors driving the biological processes involved in this attenuation are not well-known. Here, the efficiency of arsenic (As) removal was investigated in a bench-scale continuous flow channel bioreactor treating As-rich AMD (∼30-40 mg L). In this bioreactor, As removal proceeds via the formation of biogenic precipitates consisting of iron- and arsenic-rich mineral phases encrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 59 publications
7
39
0
Order By: Relevance
“…This might facilitate arsenic adsorption and/or co-precipitation. During Fe(II) oxidation, arsenic can also be co-precipitated with Fe(III), resulting in the formation of amorphous ferric arsenate (Fernandez-Rojo et al, 2017;Tian et al, 2017). In this study, although a large proportion of arsenic was co-precipitated during Fe(III) precipitation (Fig.…”
Section: Fe(ii) Oxidation With Microaerophilic Fe(ii)-oxidizing Bacteriamentioning
confidence: 60%
See 3 more Smart Citations
“…This might facilitate arsenic adsorption and/or co-precipitation. During Fe(II) oxidation, arsenic can also be co-precipitated with Fe(III), resulting in the formation of amorphous ferric arsenate (Fernandez-Rojo et al, 2017;Tian et al, 2017). In this study, although a large proportion of arsenic was co-precipitated during Fe(III) precipitation (Fig.…”
Section: Fe(ii) Oxidation With Microaerophilic Fe(ii)-oxidizing Bacteriamentioning
confidence: 60%
“…Previous reports show that arsenic is toxic to many microorganisms, which consequently affects the distribution of FeOB (Fernandez-Rojo et al, 2017). The cluster analysis showed that the structure of microbial community in the iron oxide layer was significantly affected by the presence of arsenic (Fig.…”
Section: Dominant Microorganisms For Microaerophilic Fe(ii) Oxidationmentioning
confidence: 78%
See 2 more Smart Citations
“…real-time PCR (qPCR), respectively from DNAs and cDNAs obtained from cultures of "T.arsenivorans" and H. arsenicoxydans. qPCR was carried out using m4-1F forward (GCCGGCGGGGGNTWYGARRAYA) and m2-1R reverse (GGAGTTGTAGGCGGGCCKRTTRTGDAT) primers, as designed in[30] and applied in[31]. The expected product size was 110 bp.…”
mentioning
confidence: 99%